Disaster preparation: Survey of patients with food allergies in Kobe, Japan. Issue 9 (30th September 2019) - Hirase, Satoshi; Okafuji, Ikuo; Kasai, Kazuko; Matsumoto, Kazunori; Tanaka, Yukiko; Tanaka, Yuya; Tsuruta, Satoru
Abstract: Background: Securing food for patients with food allergies may be more difficult during disasters, but reports on the status of household allergen‐free food reserves in preparation for disasters are limited. This study investigated the household stock status of allergen‐free foods in preparation for disasters in Kobe City after the Great Hanshin‐Awaji Earthquake. Methods: The survey targets were 172 parents of patients with a food allergy who underwent in‐hospital oral food challenge test for allergies at four hospitals from October 2016 to March 2017. Of these, 158 patients with allergies to eggs, milk and wheat were included in the analysis. The first survey was performed to investigate patient characteristics and stockpiling status of allergen‐free foods in parallel with oral food challenge tests. The second survey was performed on the follow‐up visit to investigate any changes in behavior. Results: Median patient age was 3 years, with boys comprising 68.4% of the patients. Eggs were the most eliminated food, and the median number of foods avoided was 2. A total of 82.3% of parents had experienced disasters. The proportion of households that stockpiled allergy‐free meals was 42.4%, and the median amount was 3 days. The stockpiling situation did not differ according to the parents' disaster experience. In the second survey, 45.3% had modified their stockpiling practice. Conclusions: Even in this area where the Great Hanshin‐Awaji Earthquake occurred, household stockpiles of allergen‐free foods are inadequate; therefore, all medical staff should educate families about the necessity of stocking allergen‐free food for disasters.